The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.3346/jkms.2014.29.7.1007
|View full text |Cite
|
Sign up to set email alerts
|

Application of Damage Control Resuscitation Strategies to Patients with Severe Traumatic Hemorrhage: Review of Plasma to Packed Red Blood Cell Ratios at a Single Institution

Abstract: When treating trauma patients with severe hemorrhage, massive transfusions are often needed. Damage control resuscitation strategies can be used for such patients, but an adequate fresh frozen plasma: packed red blood cell (FFP:PRBC) administration ratio must be established. We retrospectively reviewed the medical records of 100 trauma patients treated with massive transfusions from March 2010 to October 2012. We divided the patients into 2 groups according to the FFP:PRBC ratio: a high-ratio (≥0.5) and a low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Sensitivity studies using leave one out analysis of 24-hour and 30-day/in-hospital mortality at different ratios were done. (Supplementary figure 3) Morbidity ARDS data was available from 8 studies 2,14,28,29,35,40,45,46 and ALI data was reported in 2 studies 14,28 . There was no difference in the incidence of ARDS with respect to FFP: RBC ratio (OR: 0.68, CI 0.40-1.16, P=0.16).…”
Section: Mortalitymentioning
confidence: 99%
“…Sensitivity studies using leave one out analysis of 24-hour and 30-day/in-hospital mortality at different ratios were done. (Supplementary figure 3) Morbidity ARDS data was available from 8 studies 2,14,28,29,35,40,45,46 and ALI data was reported in 2 studies 14,28 . There was no difference in the incidence of ARDS with respect to FFP: RBC ratio (OR: 0.68, CI 0.40-1.16, P=0.16).…”
Section: Mortalitymentioning
confidence: 99%
“…Whilst such protocols have been found to reduce morbidity and mortality, [ 35 ] the requirement for such large amounts of clotting products and the exact composition of this transfusion regime does remain controversial [ 36 ]. An observational study recently demonstrated the early survival benefits of delivering clotting product to red cell ratios above 0.5:1 in patients with severe haemorrhage [ 37 ]. Conversely, recent military evidence suggests that ratios of a low as 0.35:1 may be preferable [ 38 ].…”
Section: Damage Control Resuscitationmentioning
confidence: 99%
“…Plasma contains all proteins involved in secondary hemostasis and the essential von Willebrand factor (vWF) for initiating primary hemostasis and stabilizing Factor (F) VIII in secondary hemostasis. Rapid replenishment of plasma loss is critical in the acute phase of trauma/hemorrhage under damage control resuscitation practice . Currently, fresh frozen plasma (FFP) and plasma frozen within 24 hours are the most commonly used plasma products.…”
mentioning
confidence: 99%